The subject approach to information - Foskett, A. C. (London : Bingley, 1969)
This brand new edition of the classic librarianship text will be fully updated to take in recent developments.Drawing on the research of experts from the fields of computing and library science, this ground-breaking work will show you how to combine two very different approaches to classification to create more effective, user-friendly information-retrieval systems
Includes bibliographical references and index.
aia 29/06/17
Loans
Keywords: Subject cataloging; Indexing